Defamiliarization of Power Hegemony of the Characters in Ajidarma's Kitab Omong Kosong - Prasetyo Utomo, S.; Nuryatin, Agus; A. Sayuti, Suminto; Supriyanto, Teguh (Universitas Negeri Semarang, 2018)
The intertextual study between Ajidarma’s Kitab Omong Kosong and the Ramayana romance hypogram composed by Rajagopalachari leads us to the defamiliarization of the hegemony of Rama's power, deviating to the heinous, barbaric, and harassing domination of power over the people of the Ayodya colony. In the Ramayana romance, the hegemony of Rama's power, as awatara Lord Vishnu, being honored by his people for his courage against Rahwana's wrath. The hegemony of Rama's power goes hand in hand with the moral, the virtues of life, and the dharma. Ajidarma’s Kitab Omong Kosong is marked by defamiliarization motives. The motives form a plot (sjuzet) that deviates from the Ramayana and creates the wholeness of the story (fabula) which is constructed with a unique structure. Rama's character is told by defamiliar motives that (1) deviate not far from convention, (2) balanced between convention and innovation, and (3) free oneself by convention. Ajidarma created the story of Rama with several advantages: (1) deviating the role of the characters, thus avoiding the binary opposition of black and white characters in reaching power, (2) the stories being woven in a unique story structure, alternating between myths, facts, and literary images, (3) as a whole the novel it creates presents a peculiar and unique story (fabula), and (4) the novel becomes a plural text, i.e. a text with plural interpretations.